Possibilidades e limites na utilização dos serviços de Saúde por parte dos usuários do Programa Bolsa Família - Vieira, Aline Souto Maior Normando (2010)
This work investigates the limits and possibilities for use of health services by beneficiaries of the Bolsa Família in fulfilling the conditions. Integrates research "Repercussões do Programa Bolsa Família na Segurança Alimentar e Nutricional das Famílias Beneficiárias performed by IBASE, nationwide, funded by FINEP. The analysis presented was based on information from different local actors involved with the program, beneficiaries, managers and representatives of the instances of social control in different metropolitan contexts in northern, midwestern, southeastern and southern Brazil. Material collected from semistructured interviews with managers and representatives of social control agencies and focus groups conducted with users. The municipalities studied were selected because they represent the characteristics of large cities in their respective regions. These data were analyzed considering the local context and supplemented with documentary analysis. It is concluded that the implementation of health conditionalities in the different contexts analyzed, tended to reflect the above conditions of use of health services without having driven significant advances in these processes.